Pandangan dan Tantangan Guru dalam Penerapan Metode Socrates untuk Meningkatkan Keterampilan Berpikir Kritis Siswa Sekolah Dasar - Fawaid, Achmad; Nadifah, Nadifah (Mitra PGMI: Jurnal Kependidikan MI, 2024)
Critical thinking skill is a major concern in education throughout the world, with the aim of preparing students for the learning context of the 21st century. However, many teachers have difficulty adopting this new teaching method. This qualitative research aims to investigate teachers' views and the obstacles they face when implementing the Socratic method, an inquiry-based learning approach, in the classroom. Researchers used a purposive sampling method to select five Indonesian language teachers and conducted semi-structured interviews. Data analysis shows that most teachers see positively the application of the Socratic method in improving students' critical thinking skills. However, they face challenges, especially related to knowledge of teaching materials, questioning skills, student participation, topic selection, and time constraints. Based on these findings, this research recommends the need for additional support for teachers, especially in terms of understanding Indonesian language subject matter and effective teaching skills while implementing the Socratic method in the classroom.